Heat-resistant material
Patent Information
- Application Number
- JP2022058923
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-31
- Publication Date
- 2025-03-12
AI Technical Summary
Conventional heat-resistant materials lack sufficient heat insulation performance during ignition and fail to conform to uneven surfaces, leading to heat propagation through cracks.
A heat-resistant material comprising a heat-resistant layer and a silicone foam layer, with a thermal conductivity of less than 0.2 W/m·K, capable of conforming to uneven surfaces and maintaining a surface temperature below 500°C upon ignition.
The material provides effective heat insulation and conforms to uneven surfaces, preventing heat propagation and maintaining low surface temperatures even when ignited.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to heat-resistant materials, such as those used in automobiles or batteries. [Background technology]
[0002] When a component (or part) overheats or catches fire, it can adversely affect surrounding components (or parts). Various heat-resistant materials have been proposed to eliminate or mitigate such adverse effects. For example, a challenge with lithium-ion batteries is thermal runaway due to rapid temperature increases caused by short circuits, overcharging, or over-discharging. In response to this, various heat-resistant materials have been proposed to protect adjacent batteries from the heat of a battery experiencing thermal runaway. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2021-163538 [Overview of the project] [Problems that the invention aims to solve]
[0004] The inventors of this invention have found that conventional materials have insufficient thermal insulation performance during ignition. Therefore, the primary objective of this invention is to provide a heat-resistant material that has sufficient thermal insulation performance even during ignition. Furthermore, depending on the application, it may be used on uneven surfaces. In this case, if the material does not conform to the uneven surface during assembly, cracks will occur. As a result, heat may be transmitted through the resulting cracks, and the required performance may not be satisfied. Therefore, a secondary objective of this invention is to provide a heat-resistant material that conforms to uneven surfaces. [Means for solving the problem]
[0005] One aspect of the present invention is a heat-resistant material having a heat-resistant layer and a silicone foam layer laminated on the heat-resistant layer, either directly or via another layer, characterized in that the temperature of the side opposite to the heat-resistant layer after the heat-resistant layer has been heated with a flame for 600 seconds is 500°C or less.
[0006] Another aspect of the present invention is a heat-resistant material comprising a heat-resistant layer and a silicone foam layer laminated on the heat-resistant layer, either directly or via another layer, characterized in that the thermal conductivity of the heat-resistant layer in both the planar direction and the thickness direction is less than 0.2 W / m·K.
[0007] Furthermore, another aspect of the present invention is a heat-resistant material having a heat-resistant layer and a silicone foam layer directly laminated to the heat-resistant layer. [Effects of the Invention]
[0008] According to the present invention, it is possible to provide a heat-resistant material that has sufficient heat insulation performance even when ignited. Furthermore, according to the present invention, it is also possible to provide a heat-resistant material that conforms to uneven surfaces. [Brief explanation of the drawing]
[0009] [Figure 1] Figure 1 shows an example of a heat-resistant material composed of a heat-resistant layer, a silicone foam layer, and another heat-resistant layer. [Figure 2] Figure 2 is an exploded view showing a heat-resistant material interposed between cells. [Figure 3] Figure 3 is a conceptual diagram showing the surface temperature (<300°C) of the silicone foam layer in the heat-resistant material when one cell experiences thermal runaway (800°C). [Figure 4] Figure 4 shows a battery pack comprising multiple modules, each consisting of multiple cells. [Figure 5] Figure 5 is a schematic diagram of the fire resistance test (measuring the temperature of the silicone foam layer after heating the heat-resistant layer with a flame for 600 seconds). [Figure 6]Figure 6 shows the results of the fire resistance test in the example. [Modes for carrying out the invention]
[0010] The heat-resistant material according to this embodiment is a heat-resistant material having a heat-resistant layer and a silicone foam layer laminated on the heat-resistant layer, either directly or via another layer. The heat-resistant material, the method for manufacturing the heat-resistant material, and the applications of the heat-resistant material will be described in detail below.
[0011] <<<Heat-resistant material>>> <<Overall structure>> <Layer configuration> The heat-resistant material according to this embodiment comprises a heat-resistant layer and a silicone foam layer laminated on the heat-resistant layer, either directly or via another layer. Here, it is preferable that the silicone foam layer is directly laminated on the heat-resistant layer. Furthermore, the heat-resistant material according to this embodiment may have any other layers as long as it has a heat-resistant layer and a silicone foam layer. For example, another layer may be interposed between the heat-resistant layer and the silicone foam layer. An example of another layer is an adhesive layer that joins the heat-resistant layer and the silicone foam layer when they are not directly joined. Here, the adhesive is preferably an inorganic heat-resistant adhesive. Specific examples include ThreeBond's 3700 series, an inorganic adhesive using metal alkoxides as a binder; Toagosei's Aron Ceramic (registered trademark), a one-component thermosetting adhesive mainly composed of refractory ceramics such as alumina and inorganic polymers; Audec's Ceramabond, an inorganic adhesive based on aluminum nitride, alumina, silica, or zirconia; and Taiyo Kanaami's Resbond, a heat-resistant ceramic adhesive based on quartz. In addition to the adhesive layers mentioned above, other layers besides the heat-resistant layer and silicone layer include a heat diffusion layer (for example, with a thermal conductivity of 5 to 400 W / m·K).
[0012] Furthermore, the heat-resistant material according to this embodiment may have one or both of a heat-resistant layer and a silicone foam layer in plurality. Specific examples include a heat-resistant layer / silicone foam layer, a heat-resistant layer / silicone foam layer / heat-resistant layer, a heat-resistant layer / silicone foam layer / heat-resistant layer / silicone foam layer / heat-resistant layer. For example, FIG. 1 illustrates a heat-resistant material 1 composed of a heat-resistant layer 1a1 / silicone foam layer 1b / heat-resistant layer 1a2. Note that FIG. 1 is a schematic diagram, and the size, thickness, etc. are not limited thereto. Also, the heat-resistant material according to this embodiment is not limited to only the aspect where one or both surfaces of the heat-resistant material are heat-resistant layers as in the above example, and both surfaces may be silicone foam layers (for example, silicone foam layer / heat-resistant layer / silicone foam layer). This is because even if the silicone foam on the heat runaway side deteriorates thermally and does not function as a heat insulation layer, the remaining heat-resistant layer / silicone foam layer can keep the back surface temperature at 500°C or lower.
[0013] <Thickness> The heat-resistant material according to this embodiment preferably has a total thickness of 20 mm or less. Here, as the upper limit value, for example, it is 20 mm or less, 15 mm or less, 10 mm or less, 7.5 mm or less, 7 mm or less, 5 mm or less, and as the lower limit value, for example, it is 0.1 mm or more, 0.5 mm or more, 1 mm or more, 3 mm or more. As a specific example, in the case of the use of being interposed between cells, it is preferably 0.1 mm or more and 20 mm or less. Also, in the case of the use of being disposed on the outer wall of the cell group and / or in the box for housing the cell group (module, subunit, pack, etc.) composed of a plurality of cells, it is preferably 3 mm or more and 7 mm or less.
[0014] The shape of the heat-resistant material according to this embodiment is not particularly limited, and examples thereof include a square shape, a circular shape, a shape adapted to the shape of the heat-resistant object, etc.
[0015] <<Physical properties>> The heat-resistant material according to this embodiment, after heating the heat-resistant layer with a flame {for example, a flame at 800 °C (for example, the tip)} for 600 seconds, the temperature of the silicone foam layer is preferably 500 °C or lower, 475 °C or lower, 450 °C or lower, 400 °C or lower, 350 °C or lower, 325 °C or lower, 300 °C or lower. This measurement method will be described in detail below.
[0016] (Measurement method) Heat source: Use an alcohol lamp (manufactured by Hario, alcohol lamp AL-5DB, alcohol for fuel) Flame temperature: Measured with a K-type thermocouple Measurement procedure: Prepare a sample with a heat-resistant layer laminated on one side and process it to a size of 10 cm × 10 cm. Set the sample as shown in Figure 5. Heat the center of the sample from the heat-resistant layer side with a flame for 10 minutes. Measure the surface temperature of the back surface at the time of 10 minutes with an infrared thermometer {Infrared thermometer: Manufactured by HORIBA, handy type infrared radiation thermometer (IT-340)}.
[0017] <<Heat-resistant layer>> <Material> The heat-resistant layer according to this embodiment is a layer that meets UL94 V-0. Here, a preferred heat-resistant layer is a layer made of a material containing inorganic fibers and inorganic powder. Examples of the inorganic fibers in this preferred heat-resistant layer include ceramic fibers such as glass wool, silica fiber, alumina fiber, alumina silicate fiber, and zirconia fiber, mineral fibers such as rock wool, alkaline earth silicate fiber, zirconia fiber, potassium titanate fiber, and wollastonite, etc. Further, examples of the inorganic powder in this preferred heat-resistant layer include silicate minerals such as sepiolite, talc, kaolin, mica, and sericite, synthetic silica such as magnesium carbonate, calcium carbonate, hard clay, fired clay, barium sulfate, calcium silicate, wollastonite, sodium bicarbonate, white carbon, and fused silica, natural silica such as diatomaceous earth, aluminum hydroxide, magnesium hydroxide, glass beads, etc.
[0018] <Thickness> The thickness of the heat-resistant layer in this embodiment is not particularly limited, and the lower limit is, for example, 0.05 mm or more, 0.075 mm or more, 0.1 mm or more, 0.2 mm or more, and the upper limit is, for example, 10 mm or less, 7.5 mm or less, 5 mm or less, 2.5 mm or less, 2 mm or less, 1 mm or less.
[0019] <Physical properties> (Thermal conductivity) The thermal conductivity in the planar and thickness directions of the heat-resistant layer in this embodiment is, for example, limited to less than 0.2 W / m·K, 0.175 W / m·K or less, 0.15 W / m·K or less, and 0.1 W / m·K or less, respectively, as upper limits. The lower limit is not particularly limited, but is, for example, 0.01 W / m·K or more. Here, the thermal conductivity can be measured using the xenon flash method in accordance with JIS-R1611 "Measurement of Thermal Diffusivity of Ceramics".
[0020] (Tensile strength) The tensile strength of the heat-resistant layer in this embodiment has lower limits, for example, 0.1 MPa or more, 0.5 MPa or more, 1.0 MPa or more, and 1.5 MPa or more, and upper limits, for example, 20.0 MPa or less, 15.0 MPa or less, and 10.0 MPa or less. Within this example range, more favorable conformability can be achieved. Here, the tensile strength is a value measured in accordance with JIS K6251:2010.
[0021] <<Silicone foam layer>> The silicone foam layer in this embodiment is not particularly limited and can include, for example, solid-material type silicone foam (such as Mirable silicone foam), liquid-material type silicone foam (such as two-component silicone foam), and emulsion-based silicone foam. Mirable silicone foam is a silicone foam obtained by mixing organopolysiloxane as the main raw material, blending various additives (fillers, dispersants, vulcanizing agents, etc.), kneading, and then heat-curing. By using a foaming agent (chemical foaming agent) as an additive, a foam-like silicone resin can be obtained. Two-component silicone foam is a foam formed by foaming due to gas (hydrogen) generated during curing when two liquid silicone materials are mixed and stirred, resulting in the formation of bubbles (cells). Furthermore, emulsion-based silicone foam is a foam obtained by emulsifying silicone and water to create an emulsion composition, mechanically foaming the emulsion composition, and then curing (drying) it.
[0022] <thickness> The thickness of the foam layer is not particularly limited, but the lower limit is, for example, 0.5 mm or more, 1.0 mm or more, or 1.5 mm or more, and the upper limit is, for example, 20 mm or less, 15 mm or less, 10 mm or less, or 5 mm or less.
[0023] <density> The lower limit of the density of the foam layer is, for example, 100 kg / m³. 3 More than 200kg / m 3 More than 300kg / m 3 That concludes the explanation. On the other hand, the upper limit of the density of the foamed layer is, for example, 900 kg / m³. 3 Below 800kg / m 3 Below 700kg / m 3 The following applies:
[0024] <Method for manufacturing foamed sheets 1> As a method for forming a silicone foam, there is a method of mixing and stirring a two-component liquid silicone to carry out a foaming and curing reaction. Specifically, by foaming (by the generated hydrogen gas) and curing through the following reaction carried out in the presence of a catalyst such as a platinum catalyst, a self-foaming reaction type silicone foam can be obtained.
[0025] Reaction 1: The reaction between a silanol group-containing organopolysiloxane such as hydroxy-terminated polydimethylsiloxane or a hydroxyl group-containing compound (foaming aid) and an organohydrogenpolysiloxane such as methylhydrogenpolysiloxane having SiH groups at both ends and side chains Reaction 2: The reaction between a vinyl group-containing organopolysiloxane such as dimethylpolysiloxane blocked at both ends with dimethylvinylsiloxy groups and an organohydrogenpolysiloxane such as methylhydrogenpolysiloxane having SiH groups at both ends and side chains
[0026] In addition, an inert gas such as air or nitrogen may be added when mixing and stirring the two-component liquid silicone raw material. According to this, the inert gas becomes a foaming nucleus, and a more uniform cell can be formed.
[0027] Specific examples of the platinum catalyst include chloroplatinic acid, elemental platinum, chloroplatinic acid hexahydrate, a complex of chloroplatinic acid with sym-divinyltetramethyldisiloxane, dichloro-bis(triphenylphosphine)platinum(II), cis-dichloro-bis(acetonitrile)platinum(II), dicarbonyldichloroplatinum(II), platinum chloride, platinum oxide, zero-valent platinum metal complex, for example, Karstedt catalyst, [Cp*Ru(MeCN)3]PF6, [PtCl2(cyclooctadiene)], solid platinum supported on a carrier (for example, alumina, silica or carbon black), platinum-vinylsiloxane complex {for example, Pt n (ViMe2SiOSiMe2Vi) c and Pt[(MeViSiO)4] dExamples include platinum-phosphine complexes {e.g., Pt(PPh3)4 and Pt(PBU3)4} and platinum-phosphite complexes {e.g., Pt[P(Oph)3]4 and Pt[P(Obu)3]4}. Here, in the above formulas, "Me" represents methyl, "Bu" represents butyl, "Vi" represents vinyl, and "Ph" represents phenyl, and c and d represent integers.
[0028] As the hydroxyl group-containing compound (foaming aid), alcohols such as benzyl alcohol and ethanol, and water can be used. In this case, a stock solution containing vinyl group-containing organopolysiloxane (main polymer), hydroxyl group-containing compound (foaming aid), and catalyst may be prepared as solution A, and a stock solution containing vinyl group-containing organopolysiloxane (main polymer) and organohydrogenpolysiloxane (crosslinking agent) may be prepared as solution B. The foaming reaction and curing reaction may be carried out by mixing and stirring solutions A and B. The number average molecular weight of the main polymer is preferably 500 to 100,000, more preferably 1,000 to 70,000, and even more preferably 1,500 to 50,000. The number average molecular weight refers to the value measured by gel permeation chromatography (GPC) using standard polystyrene. As described above, when using two liquids consisting of liquid A and liquid B, the mixing ratio (mass ratio) of liquid A to liquid B depends on the density and cell shape of the foam to be obtained, but is typically 100:1 to 100:50.
[0029] The above-mentioned liquid A may contain silica as a reinforcing material. The amount of silica added is not particularly limited, but is between 0% and 40% by mass based on the total mass of liquid A. Liquid A may also contain titanium dioxide, aluminum hydroxide, calcium carbonate, etc., as fillers for viscosity adjustment and / or for imparting functionalities such as strength and flame retardancy. The total content of these fillers is not particularly limited, but is between 0% and 50% by mass based on the total mass of liquid A.
[0030] The reaction time for hydrogen generation is adjusted as appropriate depending on the density of the foam to be obtained and the cell morphology. It is usually 1 to 10 minutes, preferably 2 to 6 minutes. The mixing temperature is also adjusted as appropriate depending on the density of the foam to be obtained and the cell morphology. It is usually room temperature.
[0031] Furthermore, the density of the foam layer can be adjusted by optimizing the temperature during curing foam (molding), the amount of foaming aid, and the ratio of liquid A to liquid B (amount of Si-H added).
[0032] <Method for manufacturing foamed sheets 2> Foamed sheets can also be obtained by foaming / curing a silicone emulsion composition.
[0033] Here, the silicone resin used in the silicone emulsion composition is not particularly limited as long as it contains a silane compound as a raw material monomer, and dimethyl silicone, methylphenyl silicone, and various modified silicones (e.g., amino-modified silicone, epoxy-modified silicone, polyether-modified silicone emulsion, alkyl-modified silicone emulsion, fluorine-modified silicone, etc.) can be used. The silicone emulsion composition can be produced, for example, by blending the raw material monomers of the resin component in an aqueous medium and emulsion polymerization of the raw material monomers in the presence of various additives such as emulsifiers and polymerization initiators. In addition, the silicone emulsion composition may be used by blending an emulsion containing resins other than silicone resins, such as acrylic resin, polyurethane resin, polyester resin, polyepoxy resin, etc.
[0034] By mixing the aforementioned raw materials, a silicone emulsion composition, which is the raw material mixture for the foamed sheet, is prepared (preparation step). The mixing method is not particularly limited; for example, the components can be mixed while stirring in a container such as a mixing tank. Subsequently, a predetermined foaming gas is added to the silicone emulsion composition obtained in the preparation step, and these are thoroughly mixed to create a state in which many bubbles exist in the silicone emulsion composition (foamed emulsion composition) (foaming and curing step). This foaming and curing step is usually carried out by thoroughly mixing the liquid raw material mixture for the foamed sheet obtained in the raw material preparation step with the foaming gas using a mixing device such as a mixing head. Here, the foaming gas mixed into the emulsion composition in the stirring and foaming step forms bubbles (cells) in the foam, and the density of the resulting foam is determined by the amount of foaming gas added. To adjust the density of the foamed sheet, the required weight of the foamed sheet raw material can be calculated from the desired density of the foamed sheet and the volume of the foamed sheet raw material (for example, the internal volume of the mold into which the foamed sheet raw material is injected), and the amount of foaming gas can be determined so that the desired volume is achieved with this weight. Air is mainly used as the foaming gas. Other inert gases such as nitrogen, carbon dioxide, helium, and argon can also be used. As for the foaming method, the mechanical flossing method can be used. In the mechanical flossing method, air from the atmosphere is mixed into the silicone emulsion composition by stirring it with a stirring blade or the like to induce foaming. Any stirring device commonly used in the mechanical flossing method can be used without particular restriction, such as a homogenizer, dissolver, or mechanical flossing machine. The mixing time between the silicone emulsion composition and air is adjusted appropriately depending on the density of the foam to be obtained, and is usually 1 to 10 minutes, preferably 2 to 6 minutes. The mixing temperature is adjusted as needed depending on the desired foam density and cell morphology, and is usually at room temperature.The stirring speed during mixing is preferably 200 rpm or higher (more preferably 500 rpm or higher) to create fine bubbles, and preferably 2000 rpm or lower (more preferably 800 rpm or lower) to ensure smooth discharge of the foam from the foaming machine.
[0035] <<<Manufacturing method for heat-resistant materials>>> In this embodiment, the heat-resistant material preferably has a silicone foam layer directly laminated onto the heat-resistant layer, in other words, it is preferable that the silicone foam layer and the heat-resistant layer are integrally molded laminates. This preferred heat-resistant material can be manufactured by directly applying (e.g., coating) uncured silicone foam raw material (see <Method for Manufacturing Foamed Sheet 1> and <Method for Manufacturing Foamed Sheet 2> above) onto the heat-resistant layer, followed by foaming and curing. Furthermore, this manufacturing method eliminates the need for adhesives and reduces processing steps compared to the case where adhesives are used to join the heat-resistant layer and the silicone foam layer, thus reducing costs.
[0036] <<Applications of heat-resistant materials>> The heat-resistant material according to this embodiment is useful in various applications where high thermal insulation is required (for example, for automotive and battery applications). Here, we will describe in detail the case in which it is used as a heat-resistant material for batteries. Batteries can be classified as constituent units into, for example, cells (for example, cylindrical cells, prismatic cells, laminated pouch type cells), modules containing multiple cells (for example, cylindrical modules, prismatic modules, laminated pouch type modules), and packs containing multiple modules (or multiple cells) (for example, cylindrical packs, prismatic packs, laminated pouch type packs). Here, one way in which the heat-resistant material according to this embodiment is used is to place it between adjacent cells. For example, Figure 2 is an exploded view in which the heat-resistant material 1 is interposed between cell 4a and cell 4b and between cell 4b and cell 4c. Figure 3 shows an example where, despite cell 4a experiencing thermal runaway and its surface temperature reaching nearly 800°C, heat is not transferred to the adjacent cell 4b due to the presence of the heat-resistant material 1 {In the example in Figure 3, the surface temperature of the silicone foam layer of the heat-resistant material 1 is less than 300°C; therefore, the surface temperature of the heat-resistant layer of the heat-resistant material 1 (on the cell 4b side) is also less than 300°C}. Another use of the heat-resistant material according to this embodiment is in which it is placed on the outer wall of a cell group and / or in a box housing the cell group in a cell group selected from modules, subunits, and packs composed of multiple cells. For example, Figure 4 shows a battery pack A having multiple modules A1 composed of multiple cells. The battery pack A has multiple modules A1, an upper cover A2, and a lower case A3. Here, the heat-resistant material 10 according to this embodiment (for example, a heat-resistant material consisting of a heat-resistant layer / silicone foam layer) is placed on the back surface of the upper cover A2, with the heat-resistant layer facing the modules. This makes it possible to reduce the impact on other components outside the pack caused by thermal runaway in module A1 (or its cells) within pack A. [Examples]
[0037] The present invention will be described below with reference to examples. However, the present invention is not limited to these examples.
[0038] Under room temperature conditions (25°C), the two liquids (liquid A and liquid B) shown in the table below were mixed in a mass ratio of A:B = 100:10, and stirred using a stirring device at a rotation speed of 100 rpm for a stirring time of 30 seconds. Next, the stirred material was placed on a substrate to be used as the heat-resistant layer, and a mold (thickness 0.5 mm) was placed on top of it. A PET substrate (untreated surface: plain) was placed on top of the mold. The stirred material was stretched out into a sheet-like form from above the PET substrate using a stainless steel roll. After that, the mixture was reacted at a heating temperature of 60°C for a heating time of 3 minutes, and then, with the PET substrate removed, the mixture was reacted further at a heating temperature of 120°C for a heating time of 3 minutes to form a foamed layer (silicone foam layer). After that, the mold was removed to obtain the integrally molded heat-resistant material according to Examples 1-2 and 4. On the other hand, the heat-resistant material according to Example 3 was obtained by forming a silicone foam layer using the same method as in Examples 1-2 and 4 (except for the step of placing the above-mentioned stirred raw materials on the heat-resistant material), and then joining it to the substrate using an inorganic heat-resistant adhesive. The heat-resistant layers (substrates) used were: Substrate 1 (raw materials: cellulose, glassy fiber, bentonite, fused calcined diatomaceous earth, crystalline silica, flame retardant, etc.), Substrate 2 (raw materials: cellulose, glassy fiber, zeolite, fused calcined diatomaceous earth, crystalline silica, flame retardant, etc.), Substrate 3 {raw materials: alkali earth silicate fiber (SiO2, CaO+MgO) etc.}, and Substrate 4 (raw materials: vermiculite, aramid fiber, PPS fiber, cellulose, etc.). Furthermore, the thermal conductivity of all substrates was 0.15 W / m·K or less in both the planar and thickness directions.
[0039] [Table 1]
[0040] (Density of the foam layer) The density of the foamed layer of each heat-resistant material was measured in accordance with JIS K7222:2005 "Foamed plastics and rubber - Method for determining apparent density".
[0041] (Tensile strength of the heat-resistant layer) The tensile strength of the heat-resistant layer was measured using the method described above.
[0042] (Thickness of each layer) The thickness of each layer was measured using a dial thickness gauge.
[0043] (thermal equilibrium temperature) The temperature was measured using the method described above for the heat-resistant material. The back surface temperature was measured at 10-second intervals from the start until 120 seconds, and then at 30-second intervals from 120 seconds (2 minutes) to 10 minutes. The back surface temperature at 10 minutes was defined as the thermal equilibrium temperature.
[0044] (Followability) Using an Imada Force Gauge (for 500N) with attachment A-type A-4 (mountain-shaped jig), the laminate was pressed with 20N for 5 seconds and then released, and the surface condition was visually observed. No particular change in appearance was evaluated as "A (Excellent)," and the occurrence of cracks was evaluated as "B (Good)."
[0045] The evaluation results of the heat-resistant materials for Examples 1 to 4 are shown in Table 2 and Figure 6.
[0046] [Table 2]
Claims
1. A heat-resistant layer; a silicone foam layer laminated on the heat-resistant layer directly or via another layer; having A heat-resistant material in which the temperature of a surface opposite to the heat-resistant layer is 500° C. or less after the heat-resistant layer is heated with a flame for 600 seconds, A heat-resistant material that satisfies at least one of the following (1) to (5): (1) The heat-resistant layer is a layer made of a material containing inorganic fibers and inorganic powder. (2) The heat-resistant layer has a tensile strength of 0.5 MPa or more. (3) A heat-resistant material for use between battery cells, comprising a heat-resistant layer and a silicone foam layer laminated on the heat-resistant layer directly or via another layer in the opposing direction of adjacent cells. (4) The heat-resistant layer / silicone foam layer / heat-resistant layer are laminated in this order, and the thickness of the heat-resistant layer is 0.98 mm or less. (5) The gas in the bubbles of the silicone foam layer contains either helium or argon.
2. A heat-resistant layer; a silicone foam layer laminated on the heat-resistant layer directly or via another layer; having A heat-resistant material in which the heat-resistant layer has a thermal conductivity in both a surface direction and a thickness direction of less than 0.2 W / m K, A heat-resistant material that satisfies at least one of the following (1) to (6): (1) The heat-resistant layer is a layer made of a material containing inorganic fibers and inorganic powder. (2) The heat-resistant layer has a tensile strength of 0.5 MPa or more. (3) A heat-resistant material for use between battery cells, comprising a heat-resistant layer and a silicone foam layer laminated on the heat-resistant layer directly or via another layer in the opposing direction of adjacent cells. (4) The layer is laminated in the following order: heat-resistant layer / silicone foam layer / heat-resistant layer (5) The heat-resistant layer / silicone foam layer / heat-resistant layer are laminated in this order, and the thickness of the heat-resistant layer is 0.98 mm or less. (6) The gas in the bubbles of the silicone foam layer contains either helium or argon.
3. A heat-resistant material having a heat-resistant layer and a silicone foam layer directly laminated to the heat-resistant layer, A heat-resistant material that satisfies at least one of the following (1) to (5): (1) The heat-resistant layer is a layer made of a material containing inorganic fibers and inorganic powder. (2) The heat-resistant layer has a tensile strength of 0.5 MPa or more. (3) A heat-resistant material for use between battery cells, in which a heat-resistant layer and a silicone foam layer are laminated in the opposing direction of adjacent cells. (4) The heat-resistant layer / silicone foam layer / heat-resistant layer are laminated in this order, and the thickness of the heat-resistant layer is 0.98 mm or less. (5) The gas in the bubbles of the silicone foam layer contains either helium or argon.
4. A battery comprising a heat-resistant material described in any one of claims 1 to 3.